The Asymmetry in Weight Between the Right and Left Human Humerus of Bangladeshi Population (Journal of Dentistry and Allied Science, 2025)
The present investigation aimed to study the phenomenon of asymmetry in weight between the right and left human humerus of the Bangladeshi population. This cross-sectional, descriptive study was done on 100 (43 right and 57 left) fully ossified dry human humeri in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between July 2021 and June 2022. A non-random, purposive sampling technique was adopted. The weight of the humerus was measured using a digital weighing machine. The mean (±SD) weight of the right humerus was 91.067 (±26.944) gm, and the left humerus was 93.970 (±32.227) gm. The objectives of this study were to determine the weight of the human humerus in the Bangladeshi population and to compare these findings with data from other populations for use in anatomy, forensic, and archaeological studies.Journal of Dentistry and Allied Science, Vol. 8 No 2: 8-12